2016
DOI: 10.20960/nh.580
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweihgt, obesity, abdominal-obesity and short stature of adult population of Rosario, Argentina

Abstract: ResumenIntroducción: el objetivo de este trabajo fue evaluar la prevalencia de sobrepeso, obesidad, obesidad abdominal y baja estatura entre la población adulta de Rosario (Argentina). Material y métodos: se llevó a cabo un estudio nutricional transversal en Rosario (2012Rosario ( -2013, entrevistando una muestra aleatoria (n = 1.194) de la población adulta (18-70 años). Se realizaron mediciones antropométricas y un cuestionario general de características sociodemográfi cas, estilo de vida, nivel de educación … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
6
5
0
2
Order By: Relevance
“…Even in this relatively poor population of rural Northeast China, lifestyle has also been found to be related to both general and central obesity. In the present study, transition into or out of marriage, lower family income, eating more meat, and lower physical activity levels were also independent risk factors for general and central obesity, as seen in previous studies [21, 26, 27]. Numerous lines of evidence indicate that lower educational attainment shows the strongest consistent relationship with obesity [2830].…”
Section: Discussionsupporting
confidence: 88%
“…Even in this relatively poor population of rural Northeast China, lifestyle has also been found to be related to both general and central obesity. In the present study, transition into or out of marriage, lower family income, eating more meat, and lower physical activity levels were also independent risk factors for general and central obesity, as seen in previous studies [21, 26, 27]. Numerous lines of evidence indicate that lower educational attainment shows the strongest consistent relationship with obesity [2830].…”
Section: Discussionsupporting
confidence: 88%
“…While the national health survey relies on self-reported information, by contrast, our study collected data using standard body measurements and blood test analysis. Two recent research studies conducted in Argentinian cities, using anthropometric measurements, also reported higher prevalence of overweight (32.7% and 34%), and of obesity (17% and 23.5%) in the general population [48,49]. It is striking to observe that in our study, the BMI of almost three out of every four adults was above normal.…”
Section: Discussionsupporting
confidence: 69%
“…Hence, the prevalence of hypertension, hypercholesterolemia and diabetes might be underestimated for this population. This may be associated with escalating unhealthy lifestyle behaviors among Argentinians [48,49]. A study assessed the accuracy of self-reported prevalence of diabetes among people who had recently checked blood glucose levels versus those who had not, and found that the prevalence was significantly lower in the latter group [78].…”
Section: Discussionmentioning
confidence: 99%
“…The prospective Nurses’ Health Study [ 13 ] including 1922 women revealed that total adiponectin concentrations were 24% higher and HMW adiponectin concentrations were 32% higher in women from the highest quartile of adherence to the Alternate Healthy Eating Index (AHEI) compared to the women from the lowest quartile. Similar results were obtained by Volp et al [ 14 ] who demonstrated a direct significant correlation between Healthy Eating Index and adiponectin concentrations.…”
Section: Diet-related Factors With a Positive Influence On Adiponectin Concentrationssupporting
confidence: 91%